2005
DOI: 10.1088/0963-0252/14/3/009
|View full text |Cite
|
Sign up to set email alerts
|

Chamberless plasma deposition of glass coatings on plastic

Abstract: A chamberless, remote plasma deposition process has been used to coat silicon and plastic substrates with glass at ambient conditions. The films were deposited by introducing an organosilane precursor into the afterglow of an atmospheric plasma fed with helium and 2 vol% oxygen. The precursors examined were hexamethyldisilazane, hexamethyldisiloxane, tetramethyldisiloxane, tetramethylcyclotetrasiloxane and tetraethoxysilane. With hexamethyldisilazane, glass films were deposited at rates of up to 0.25 µm min −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 33 publications
3
57
0
Order By: Relevance
“…[7] In other words, the major part of film growth rate-controlling step is the adsorption of depositing plasma species in APP. Moreover, this result is consistent with several researches [8,9] that state that the substrate temperature plays a significant role in APP deposition process.…”
Section: Substrate Temperature Dependence Of the Deposition Processsupporting
confidence: 93%
See 1 more Smart Citation
“…[7] In other words, the major part of film growth rate-controlling step is the adsorption of depositing plasma species in APP. Moreover, this result is consistent with several researches [8,9] that state that the substrate temperature plays a significant role in APP deposition process.…”
Section: Substrate Temperature Dependence Of the Deposition Processsupporting
confidence: 93%
“…The ratio of the shoulder area of Si-O stretching mode (between 1140 and 1160 cm −1 ) to the primary peak area (between 1070 and 1080 cm −1 ) from the FTIR spectra has been correlated with the porosity degree of SiO x film [9] and the estimation result is shown in Table 1. It was found that the film with higher porosity degree and C/O ratio was obtained at lower deposition substrate temperature (e.g.…”
Section: Chemical Structure Of the Deposited Sio X Filmsmentioning
confidence: 99%
“…Comparison of this data with the infrared spectra of Figure 5 indicates that the poor abrasion resistance observed in the latter case is most likely due to higher porosity and to the incorporation of methyl groups into the glass matrix. [72] These results clearly indicate that the organosilicon precursor used in the PECVD process strongly influences the chemical and mechanical properties of the glass films.…”
Section: ±1mentioning
confidence: 76%
“…Note that this is a remote PECVD process, where the substrate is not in contact with the plasma, so there is no ion bombardment of the surface. The films have been deposited on both silicon substrates and plastic coupons at temperatures below 100 C. [72] The precursors examined in this study were hexamethyldisilazane (HMDSN), hexamethyldisiloxane (HMDSO), tetramethyldisiloxane (TMDSO), tetramethylcyclotetrasiloxane (TMCTS), and tetraethoxysilane (TEOS). Shown in Figure 4 is a plot of the deposition rate as a function of the precursor partial pressure for all these chemicals.…”
Section: Pecvd Of Silicon Dioxidementioning
confidence: 99%
See 1 more Smart Citation